Circular RNA expression alterations in extracellular vesicles isolated from murine heart post ischemia/reperfusion injury. (1st December 2019) - Ge, Xinyu; Meng, Qingshu; Zhuang, Rulin; Yuan, Dongsheng; Liu, Jing; Lin, Fang; Fan, Huimin; Zhou, Xiaohui
Abstract: Background: Increasing studies indicated the involvement of extracellular vesicles (EVs) in cardiovascular diseases. However, the role of circular RNAs (circRNAs) in cardiac EVs (cEVs) during ischemia/reperfusion (I/R) injury remain unclear. Methods: We isolated the cEVs from I/R injured hearts and performed RNA sequencing (RNA-seq) to identify the profile of circRNA in cEVs and investigated their potential roles in I/R pathological process. Results: Cardiac I/R induced a significantly elevated release of EVs in heart within 24 h. RNA-seq of cEVs identified 185 significantly differentially expressed (DE) circRNAs including 119 down-regulated and 66 up-regulated circRNAs in I/R group compared with the sham. GO and pathway analysis showed that these DE-circRNAs were associated with protein binding and kinase activator activity and mainly involved in the metabolic process. The circRNA-miRNA analysis exhibited the broad potentials of the DE-circRNAs to regulate target genes by acting on the miRNAs. Conclusions: These findings revealed for the first time the specific expression pattern of circRNAs in EVs derived from sham and I/R heart tissues and provided some potential targets and pathways involving in I/R injury which may provide important evidences for the role of both circRNA and EVs in the pathology of cardiac I/R. Highlights: We firstly showed the specific expression of circRNAs in cEVs post I/R injury. I/R injury contributed to the elevated release of EVs in heart tissues. Cardiac EVs can transfer into the cardiomyocytes and non-cardiomyocytes. The differentially expressed circRNAs mainly participate in the metabolic process.